ANALISIS PENGARUH ARUS KAS DAN LABA AKUNTANSI TERHADAP RETURN SAHAM - Nahdhiyatus Sholekhah, 10.05.52.0173; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2016)
The financial statements of the company used by investors to predict the stock securities. Stock securities is influenced by the amount of flow yield (return) will be obtained in the future. The performance parameters of the company that received the most attention from investors and creditors of the financial statements is profit and cash flow. This study aimed to analyze the effect of cash flow and profit accounting on stock returns of companies listed on the Indonesia Stock Exchange 2012-2013. Data obtained from the Indonesian Capital Market Directory 2012, 2013. The sample in this study as many as 61 companies out of 155 companies listed in the Indonesia Stock Exchange. Data analysis used noremalitas, classic assumption test, and test models. Test the hypothesis using statistical test T. The results showed that the operating cash flow positive and significant impact. While the investment cash flow, cash flow financing, and accounting income does not affect the Stock Return.Keywords: Return Share, Operating Cash Flow, Cash Flow Investment, Financing,Â  Cash Flow Accounting Earnings